Pengaruh Costumer Relationship Management, Service Quality dan Fasilitas Terhadap Kepuasan Pelanggan Pada Hotel Grand Inna Medan - Prassty, Andini; Parhusip, Austin Alexander (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to determine the effect of Customer Relationship Management, Service Quality and Facilities on Customer Satisfaction. The type of research used in this study is quantitative research. The research approach used in this study is an associative approach. In determining the research sample, the author uses the lemeshow formula which automatically obtains 100 samples. Data were collected using a questionnaire that has been tested for validity and reliability and processed using SPSS 26. Based on the results of the partial test, the Customer Relationship Management variable has no significant effect on customer satisfaction at the Grand Inna Medan hotel, a value of T count of 1.887 <1.985 T table was obtained, then the Service Quality variable has a positive and significant effect on customer satisfaction, a value of T count of 2.817> 1.985 T table was obtained, and the facility variable has a positive and significant effect on customer satisfaction with a value of T count of 9.504> 1.985 T table. The results of simultaneous testing show that the variables Customer Relationship Management (X1), Service Quality (X2) and facilities (X3) together have a positive and significant effect on customer satisfaction at the Grand Inna Medan hotel.